2013
DOI: 10.1038/jes.2013.52
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-based PM concentrations and their application to COPD in Cleveland, OH

Abstract: A hybrid approach is proposed to estimate exposure to fine particulate matter (PM2.5) at a given location and time. This approach builds on satellite-based aerosol optical depth (AOD), air pollution data from sparsely distributed Environmental Protection Agency (EPA) sites and local time–space Kriging, an optimal interpolation technique. Given the daily global coverage of AOD data, we can develop daily estimate of air quality at any given location and time. This can assure unprecedented spatial coverage, neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…(1) Model predictability: MLR was commonly used in early studies [17,20,21,[24][25][26][39][40][41]46,47,49,50,54,75], whereas MEM and CTM gradually became the dominant methods and replaced MLR after 2010. However, GWR has developed at a slower pace with a limited number of studies to data, and had moderate performance [32,74,125,126].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Model predictability: MLR was commonly used in early studies [17,20,21,[24][25][26][39][40][41]46,47,49,50,54,75], whereas MEM and CTM gradually became the dominant methods and replaced MLR after 2010. However, GWR has developed at a slower pace with a limited number of studies to data, and had moderate performance [32,74,125,126].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in order to improve model performance, some studies have explored covariate factors in the MLR model under different conditions [17,20,21,[24][25][26][39][40][41]46,47,49,50,54,75]. A few covariate factors, such as relative humidity and height of the boundary layer, were regarded as significant enough to affect and even invert the relationships between AOD and PM 2.5 .…”
Section: Theory Background and Applicationmentioning
confidence: 99%
“…In order to advance environmental and human health studies, mobile air pollution monitors are increasingly used to obtain more accurate personal exposure estimates. Studies show that personal sampling of air pollution is preferable when attempting to accurately measure human exposure (Good et al, 2015;Steinle et al, 2013;Weichenthal et al, 2011;Zartarian et al, 2007), and that a high spatiotemporal resolution is required to correct for misinterpretation of actual exposure (Baxter et al, 2013;Kumar et al, 2013). Although there is a lack of concrete information on the effective use of such sensors by individuals and communities, specific vulnerable populations in urban areas could benefit from these sensor systems (e.g.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Surfaces of these carbonaceous particles provide a platform to intermix with various chemicals such as metals and organics, which can increase the toxicity of the particles. Epidemiological evidence shows that particulate matter (PM) at levels typically found in urban areas are considered to have adverse health effects, including exacerbation of pre-existing respiratory diseases (Kumar et al, 2013;Díaz-Robles et al, 2015). For example, Kumar et al (2013) observed that the 2.3% risk of an acute exacerbation of chronic obstructive pulmonary disease (COPD) could be increased by a unit increase in exposure to PM of less than 2.5 µm in aerodynamic diameter (PM 2.5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological evidence shows that particulate matter (PM) at levels typically found in urban areas are considered to have adverse health effects, including exacerbation of pre-existing respiratory diseases (Kumar et al, 2013;Díaz-Robles et al, 2015). For example, Kumar et al (2013) observed that the 2.3% risk of an acute exacerbation of chronic obstructive pulmonary disease (COPD) could be increased by a unit increase in exposure to PM of less than 2.5 µm in aerodynamic diameter (PM 2.5 ). Notably, the prevalence rate of COPD in South Asia was 4.2%-9.4% as reported by Lim et al (2015) in 2015, suggesting that characterization of PM emitted by biomass burning is urgent for public health.…”
Section: Introductionmentioning
confidence: 99%